Implementation Of The Student Teams Achievement Divisions (STAD) Cooperative Learning Model To Improve Student Learning Outcomes In The Teaching Profession Course At Pamulang University - Saptina Retnawati; Indah Pertiwi; Marissa Ulfa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this research is to enhance students’ academic performance through the application of the Cooperative Learning model, specifically the Student Teams Achievement Divisions (STAD) type, in the Teaching Profession course at Universitas Pamulang. This research is a classroom action research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 21 students in the even semester of the 2024/2025 academic year. The instruments used included learning outcome tests, student activity observation sheets, response questionnaires, documentation, and lecturer reflection notes. The results showed an increase in the average score from 72.5 in the first cycle to 80.1 in the second cycle, and an improvement in the number of students achieving mastery from 13 students (61.9%) to 19 students (90.5%). Observations indicated greater student engagement, participation, and collaboration in group activities. Students also responded positively to the STAD model, suggesting that the method fosters an active and cooperative learning environment. Therefore, the STAD learning model is effective in improving student learning outcomes, both cognitively and affectively.